ANALISIS PENERAPAN NILAI RETURN ON EQUITY (ROE), PRICE EARNING RATIO (PER), PRICE TO BOOK VALUE (PBV), DAN DEBT TO EQUITY RATIO (DER) DALAM PENGAMBILAN KEPUTUSAN INVESTASI SAHAM PADA SEKTOR PERBANKAN DI BEI SELAMA PERIODE 2019-2023 - Sihombing, Hagai Fransiska; Williams, Jerry; Sitorus, Jessy Safitri; Sanjaya, Made Wulandari Sari (POLITEKNIK LP3I JAKARTA, 2026)
The development of the capital market in the banking sector requires investors to accurately analyze financial information in making stock investment decisions. The dynamics of the banking industry in Indonesia, influenced by changing economic conditions and market uncertainty, underline the importance of this study. This research aims to analyze the effect of Return on Equity (ROE), Price Earnings Ratio (PER), Price to Book Value (PBV), and Debt to Equity Ratio (DER) on stock investment decisions in banking companies listed on the Indonesia Stock Exchange. This study employs a quantitative approach using secondary data derived from annual financial statements of banking companies. The sample is determined through a purposive sampling method. Data analysis is conducted using multiple linear regression, with hypothesis testing carried out through partial tests, simultaneous tests, and the coefficient of determination. The results indicate that ROE, PER, PBV, and DER have a significant effect on stock investment decisions. These variables are able to explain variations in investment decisions, while other factors outside the model also contribute.